2019
DOI: 10.1109/access.2019.2902570
|View full text |Cite
|
Sign up to set email alerts
|

Tradeoff Between Secrecy Capacity and Harvested Energy for Secure Visible Light Communications With SWIPT

Abstract: By considering the threefold roles of indoor visible light communications (VLC), i.e., illumination, secure information transmission, and light power transfer, the tradeoff between the secrecy capacity (SC) and the harvested energy (HE) is investigated in this paper. An indoor VLC system consisting of a transmitter, a legitimate receiver, and an eavesdropper is established. The legitimate receiver can perform secure information transmission and light power transfer simultaneously, while the eavesdropper is jus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…The received optical signals at D and E are converted to electrical signal through PD. Then, we apply the maximal ratio combining (MRC) scheme at the legitimate user and eavesdropper to merge the signals from S and R [22]. Therefore, the final SNRs of the legitimate user and eavesdropper are given by, γD=minγSR,γRD+γSD, γE=minγSR,γRE+γSE.…”
Section: System and Channel Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…The received optical signals at D and E are converted to electrical signal through PD. Then, we apply the maximal ratio combining (MRC) scheme at the legitimate user and eavesdropper to merge the signals from S and R [22]. Therefore, the final SNRs of the legitimate user and eavesdropper are given by, γD=minγSR,γRD+γSD, γE=minγSR,γRE+γSE.…”
Section: System and Channel Modelsmentioning
confidence: 99%
“…To the best of our knowledge, we found that a few researchers studied the PLS for the mixed VLC/RF communication systems. The tradeoff between the secrecy capacity (SC) and the harvested energy (HE) is investigated in VLC system, which receiver is employed to coordinate the information decoding and the EH using simultaneous wireless information and power transfer in [22]. A cooperative hybrid VLC/RF system with spatially random terminals is considered in [23].…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, the power splitter at Eve divides ρ (0 < ρ ≤ 1) portion of the signal power for ID, and the remaining (1 − ρ) portion of power for EH [18]. Therefore, the received signals at Bob and Eve are given, respectively, by [19]…”
Section: System Modelmentioning
confidence: 99%
“…where C th = 0.5 ln (γ th ) denotes the threshold of the target SC, and γ th ≥ 1 denotes the equivalent threshold of the SNR. It should be noted that it is very challenging to obtain a closed-form expression of (19). Alternatively a tight lower bound of SOP is given in the following.…”
Section: A Statistical Characteristic Analysismentioning
confidence: 99%
“…More recently, VLC has been proven to be capable of EH in both free-space [4] and underwater [5],empowering a new perspective on simultaneous lightwave information and power transfer (SLIPT) [6]. For instance, Wang, et al in [7] investigated the indoor SLIPT system taken into account the tradeoff between the secrecy capacity and the harvested energy. Tang, et al in [8] investigated joint subchannel assignment and power allocation to solve the mixed-integer frac-tional nonlinear programming problem in the energy efficiency optimization of SLIPT.…”
Section: Introductionmentioning
confidence: 99%